FP 1411 - Adam Matthew Digital (Firm) (Marlborough, Wiltshire : Adam Matthew Digital, 2007)
Letter, 26 Aug 1677
AMDigital Reference:FP 1411.
Virginia Company Archives.
Magdalene College, Cambridge
English
Keywords: London; London (England); Little Gidding; Ferrar, Ann; Ferrar, Ann; Ferrar IV, John; Ferrar, Rev Thomas; Ferrar, Virginia; Ferrar, Virginia